Assessment of Cyber Security Awareness Using Developed Game From H5P on Users Aged at Elementary and First Secondary School in Madiun City - Andria, Andria; Laksono, Ridam Dwi; Sussolaikah, Kelik; Mat Din, Mazura Binti; Mansor, Shaifizat; Dawam, Siti Rafidah Muhamat (Journal of Applied Engineering and Technological Science (JAETS), 2025)
The increasing cyber threats among children using digital devices without supervision highlight the importance of early cybersecurity awareness. This study aims to develop and evaluate an H5P-based educational game to enhance cybersecurity awareness among elementary and junior high school students in Madiun City. Using a Research and Development (R&D) approach, the game was developed through four stages: needs analysis, design and development, expert validation, and limited field testing. The game incorporates gamification elements such as points, badges, and instant feedback to engage students in learning topics such as password management, data protection, and phishing recognition. The results indicate that 70% of 68 elementary students and 74% of 92 junior high school students showed improved awareness after playing the game. These findings suggest that interactive educational games can effectively enhance cybersecurity awareness among children. The study recommends broader implementation of gamified approaches in educational curricula to foster safe online behavior from an early age.